Indigenous disparity in lower court imprisonment decisions: a study of two Australian jurisdictions, 1998 to 2008 - Christine Bond
This paper reports findings from statistical analyses of Indigeneity and lower court sentencing in New South Wales and South Australia from 1998 to 2008. The aim was to explore the probability of Indigenous versus non-Indigenous defendants receiving a prison sentence over time, while controlling for other key sentencing determinates (ie sex, age, criminal history, seriousness of current offence, plea, bail status). Across the study period, results generally showed that Indigenous offenders were more likely to receive a prison term than similarly situated non-Indigenous offenders. However, the pattern of disparity over time differed by jurisdiction. In New South Wales, Indigenous offenders were more likely to receive a prison sentence throughout the entire period. By contrast, in the South Australian lower courts, disparity was found to have increased, with earlier years showing parity and leniency, before a trend towards a greater likelihood of a prison sentence for Indigenous offenders. Focal concerns theory is used to provide a possible explanation for the study’s finding of Indigenous lower court sentencing disparity